KAJIAN AYAT L? YUKALLIFULL?HU NAFS?N ILL? WUS‘AH? (QS. AL-BAQARAH: 286) SEBAGAI LANDASAN KONSEP PENDIDIKAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA - Albaab, Ahmad Sahilul; Thobroni , Ahmad Yusam (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2025)
Differentiated education, initiated in the Merdeka Curriculum, aims to adjust teaching methods to meet the diverse needs, learning styles, and abilities of students in a class, ensuring that students do not feel pressured or left behind compared to others and preventing stress-related issues. In the Qur'an, specifically in Surah Al-Baqarah (2:286), which says, La Yukllifullahu Nafsan Illa Wus'Aha, Allah does not burden anyone beyond their capacity. While this verse addresses burdens in worship, it holds relevance in the context of education. Therefore, this study aims to explore this verse as a foundation for the concept of differentiated education in the Merdeka Curriculum. This research uses a qualitative descriptive method with a literature study approach, analyzing several Qur'anic interpretations and journals related to differentiated education. The results of this study indicate that the verse La Yukllifullahu Nafsan Illa Wus'Aha provides a strong foundation for creating inclusive learning that aligns with students' capacities, in line with Islamic values of justice and respect for individual abilities.